MENGEVALUASI HUKUMAN KEBIRI DAN PENTINGNYA FATWA MAJELIS ULAMA INDONESIA - Moh Rasyid (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2019)
Children need protection and guidance from adult people to become a quality generation. Relationship between children and adult people in their surrounding community plays significant role in children development. However, in some case, adult people cause suffering for children such as in the case of child abuse or violence. Meanwhile, the regulation concerning child fails to provide protection for children. Due to the rise of crime against children, President Joko Widodo signed Perppu No 1/2016, later on became the Law no 17/2016, which threatened the actor of child abused to be emasculated. Human right activists and medical experts were opposing the law. Despite the debate between the proponents and the opponents of castration, including among Moslems, the Council of Indonesian Ulama (MUI) did not published fatwa concerning this matter. The most important thing is protecting children from being abused by empowering education and restorative justice.